Tuberculous Epididymitis Mimicking a Testicular Tumour: A Case Report - Adem Altunkol; Yalçın Evliyaoğlu; Nevzat Can Şener (Journal of Urological Surgery, 2015)
Tuberculosis is a disease that affects almost every organ. The diagnosis and treatment of primary genitourinary tuberculosis is cumbersome and often requires invasive procedures for diagnosis. It is mandatory to differentiate tuberculous epididymitis from other causes of intrascrotal diseases such as bacterial epididiymitis and tumors. We discussed a case of tuberculous epididymitis presenting with a scrotal mass, to emphasize that tuberculous should also be considered in the differential diagnosis, besides malignancy